Time of methyl jasmonate application influences the development of ‘Cripps Pink’ apple fruit colour - Shafiq, M.; Singh, Zora; Khan, A. (John Wiley and Sons Inc., 2013)
Background: The effects of time and numbers of pre-harvest sprays of methyl jasmonate (MJ) on the development of red blush, export-grade fruit, accumulation of flavonoids in fruit skin and quality of ‘Cripps Pink’ apple were investigated in 2005 and 2006. In the first experiment during 2005, whole trees were sprayed once with 10 mmol L−1 MJ at weekly intervals from 155 to 183 days after full bloom (DAFB). In second experiment during 2006, different numbers of sprays (0, 1, 2, 3, 4, 5 or 6) of 5 mmol L−1 MJ were applied from 151 to 179 DAFB. Results: A single spray of MJ (10 mmol L−1) at 169 DAFB resulted in the highest increase in the red blush, export-grade fruit, accumulation of anthocyanins, cyanidin 3-galactosides, chlorogenic acid, phloridzin, flavanols and flavonols in fruit skin as compared to all other treatments without affecting fruit quality. A single spray of 5 mmol L−1 MJ at 186 DAFB was more effective in improving red blush, export-grade fruit and accumulation of anthocyanins in fruit skin as compared to its multiple applications. The exposed sides of fruit developed better colour than the shaded sides, regardless of time and numbers of MJ sprays. Time of a single spray of MJ is more effective than its multiple applications. Conclusions: A single pre-harvest spray of MJ (10 mmol L−1) at 169 DAFB or MJ (5 mmol L−1) at 186 DAFB was effective in improving the red blush and export grade fruit through accumulation of flavonoids in fruit skin without adversely affecting quality at harvest.